1996
DOI: 10.1063/1.361250
|View full text |Cite
|
Sign up to set email alerts
|

Possible evidence for quantum-size effects in self-assembled ultrathin films containing conjugated copolymers

Abstract: We present photoluminescence (PL), UV absorption, electroluminescence and x-ray reflectivity studies of self-assembled multilayer films containing alternate layers of conjugated copolymers, and nonconjugated insulating polymers. We show that the PL emission properties of these organic quantum wells can be ‘‘tuned’’ by a proper choice of the conjugated copolymer and the thickness of the insulating layers. Particularly, some of the self-assembled ultrathin films containing thin (∼7 Å) insulating polymeric layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 19 publications
4
29
0
Order By: Relevance
“…Also, their smooth surface renders them well suited for X-ray reflectivity studies 131,312,381,382,385) and for near-field microscopy. For these purposes, mica 75,103,104,201,252,253,281,316,323,348,386,387) and float glass 19,80,131,180,182,184,185,388,389) present alternatives. Gold coated surfaces enable electrochemical studies 86,196,205,209,211,340,354,390,391) , investigations by quartz crystal microbalance (QCM) 65,86,102,119,130,202,238,266,279,305,338,339,350,…”
Section: Useful Substratesmentioning
confidence: 97%
“…Also, their smooth surface renders them well suited for X-ray reflectivity studies 131,312,381,382,385) and for near-field microscopy. For these purposes, mica 75,103,104,201,252,253,281,316,323,348,386,387) and float glass 19,80,131,180,182,184,185,388,389) present alternatives. Gold coated surfaces enable electrochemical studies 86,196,205,209,211,340,354,390,391) , investigations by quartz crystal microbalance (QCM) 65,86,102,119,130,202,238,266,279,305,338,339,350,…”
Section: Useful Substratesmentioning
confidence: 97%
“…The ellipsometry spectra of the multilayered structure were simulated using the WVASE Software [8] taking into account the previously determined optical constants of Alq 3 and α-NPD. The thickness for all Alq 3 (α-NPD) layers was considered to be the same in the stack.…”
Section: Multilayer Structurementioning
confidence: 99%
“…More specifically, the PL and EL spectra of films with an organic quantum well structure are blue-shifted by the increased exciton binding energy due to the quantum confinement effect in a potential well [18][19][20][21]33,34]. Hong et al reported that, in the case of adsorbing the relatively thick insulating layer (about 3-5 nm), PL spectra of dipassembled (PPV/PSS) n or (PPV/PAA) n multilayer films are blue-shifted because these insulating layers effectively screen the interpenetration between neighboring PPV layers [35,36]. In this view, it should be noted that the respective PMAA layers of about 1.0 nm thickness can separate PPV layers inducing the blue shift in the PL and EL spectra of spin-assembled EL devices due to the relatively low level of interpenetration between the PPV and PMAA layers (i.e., the distinct interface between the two layers).…”
Section: Photoluminescence and Electroluminescence Spectramentioning
confidence: 96%